2003
DOI: 10.1074/jbc.m213032200
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-sensitive Lipase Null Mice Exhibit Signs of Impaired Insulin Sensitivity whereas Insulin Secretion Is Intact

Abstract: Lipid metabolism plays an important role in glucose homeostasis under normal and pathological conditions. In adipocytes, skeletal muscle, and pancreatic ␤-cells, lipids are mobilized from acylglycerides by the hormone-sensitive lipase (HSL). Here, the consequences of a targeted disruption of the HSL gene for glucose homeostasis were examined. HSL null mice were slightly hyperglycemic in the fasted, but not fed state, which was accompanied by moderate hyperinsulinemia. During glucose challenges, however, dispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
168
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(189 citation statements)
references
References 51 publications
16
168
5
Order By: Relevance
“…Therefore, it seems likely that the expression of Hsl is higher in ZF islets, which is consistent with the enzyme activity data. The role of HSL in islet beta cell function is unclear, however, as insulin secretion has been shown to be little or not affected in Hsl −/− animals [18,31]. We showed impaired GSIS in only male fasted Hsl −/− mice, and this was completely reversed by the provision of exogenous NEFA [18].…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it seems likely that the expression of Hsl is higher in ZF islets, which is consistent with the enzyme activity data. The role of HSL in islet beta cell function is unclear, however, as insulin secretion has been shown to be little or not affected in Hsl −/− animals [18,31]. We showed impaired GSIS in only male fasted Hsl −/− mice, and this was completely reversed by the provision of exogenous NEFA [18].…”
Section: Discussionmentioning
confidence: 64%
“…A tight regulation of hepatic TAG synthesis, hydrolysis and b-oxidation is required to prevent lipid accumulation. HSL was initially observed in adipose tissue, but observations in mice suggest that HSL is also expressed in liver (Mulder et al 2003;Reid et al 2008;Sekiya et al 2008). Hepatic overexpression of HSL (in cells) is shown to reduce hepatic steatosis by promoting b-oxidation, and it has therefore been suggested that HSL may be a therapeutic target for the treatment of fatty liver in human subjects (Reid et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…cytes, muscle, liver (27), and islets, 2 as obviated by studies of HSL null mice, whereas the diglyceride lipase activity in tissues of this model is comparatively more retained. Recently, cholesterol has been suggested to play a role in signaling leading to glucose-stimulated insulin secretion (28), opening for speculation that HSL acts, via cholesterol release, to affect insulin secretion.…”
Section: Fig 2 Detection Of Hsl Exon a In Transcripts From Rat Tissmentioning
confidence: 93%